Analisis Energi Aktivasi Pada Variasi Kecepatan Udara Dan Laju Reaksi Pembakaran Briket Limbah Kelapa Tua, Kelapa Muda Dan Kakao - Wahidin Nuriana; Agus Suryanto; Mustafa Kamal (JURNAL AGRI-TEK : Jurnal Penelitian Ilmu-Ilmu Eksakta, 2019)
The purpose of this study was to obtain activation energy with the rate of combustion air, reduced mass weight and reaction rate of combustion of charcoal briquettes from biomass waste of old coconut, young coconut, cacao waste with carbonization at a temperature of 400oC, for 30, 60, 90 and 120 minutes. The study was conducted in a laboratory, with 3 (three) repetitions. The study was carried out by sorting raw materials, chopping, drying, carbonizing, grinding, sifting, adding tapioca glue to print, and pressing at 115 kg / cm2. The results of the briquette were analyzed for heat, the highest calorific value of old coconut waste, young coconut, cocoa waste was analyzed for activation energy during the combustion process using DSC by varying the air heating rate of 20, 30, 40 ml / minute. The highest yield of old coconut briquette heating value is 6,927 cal/g with 90 minutes carbonization time. The lowest activation energy is 133.20 joules / gram on old coconut briquettes with an air speed of 40 ml / minute. In the rate of combustion reaction by thermogravimetry with Thermal Gravimetry Analyzer (TGA), the greatest reduction in mass weight on old coconut waste briquettes compared to young coconut and cocoa waste briquettes was 55.34% from 590.5 oC to 599.2 oC.